Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

Comparison of Branched DNA to RT-qPCR Technology for the Quantitation of mRNA from mRNA-LNP Drug Product in Human Serum - Carl A. Luongo; Ashley D. Wright; Timothy L. Lochmann; Sweilem B. Al Rihani; Jean-Claude Marshall; Darshana Jani; Jason Pennucci; Jessica Ortiz (The AAPS Journal, 2025)